Review of state of the art for metaheuristic techniques in academic scheduling problems - Chong, Keat Teoh (Springer Netherlands, 2015)
The Academic Scheduling Problems have drawn great interest from many researchers of various fields, such as operational research and artificial intelligence. Despite the long history of literature, the problem still remains as an interesting research topic as new and emerging metaheuristic techniques continue to exhibit promising results. This paper surveys the properties of the Academic Scheduling Problems, such as the complexity of the problem and the constraints involved and addresses the various metaheuristic techniques and strategies used in solving them. The survey in this paper presents the aspects of solution quality in terms of computational speed, feasibility and optimality of a solution.